Assessment of Serum Levels of Salusin ? and Salusin ? in Cardiovascular Disease Patients Undergoing Transcatheter Therapy - Ayat Saeed Awad*1, Hanaa Addai Ali2 , Mohauman Mohammad AL-Rufaie 3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Cardiovascular disease (CVD) covers some disorders, such as the diseases of the cardiac muscles and the vascular system supplying the heart, brain and extra vital organs. CVD morbidity and mortality is mainly due to coronary heart disease and cerebro-vascular diseases. The aims of the present is to measure the levels of Salusin ?, Salusin ?, lipid profile, fasting blood sugar, insulin, insulin resistance and HOMA IR in the serums of cardiovascular patients who are subject to catheterization and to compare these levels with the ones of the healthy group and their correlation with Salusins. The results have made use of the appropriate statistical methods. The results of the research have shown that there is a significant increase in the salusin-? in CVD patients compared with that of the healthy group but Salusin ? (p›0.001) witnessed a significantly lower level. The present study has demonstrated that VLDL.C, HDL.C, TG.C and Salusin-? are in a significant correlation with Salusin ?. Also, Age, BMI, HOMA-?, Insulin, HOMA-IR, FBG, CHO and LDL.C have no significant correlation with Salusin ?. The results have shown that BMI and Salusin ? levels are significantly correlated with salusin-?. In addition, Age, HOMA-?, Insulin, HOMA-IR, FBG, CHO, LDL.C, VLDL.C, HDL.C and TG.C have no significant correlation with Salusin-?. BMI and HDL.C have shown a positive correlation with Salusin ?. Moreover, Age, Insulin, HOMA-IR, HOMA-?, FBG ,CHO, LDL.C, VLDL.C and TG.C have shown a positive correlation with Salusin-?.